Regulating the Audit Quality and Deprofessionalisation of the Auditing Profession - Sulaiman, Noor Adwa; Muhamad, Rusnah; Abdullah, Mazni (Asian Journal of Accounting Perspectives, 2014)
There has been considerable criticism of the auditing profession from the public following a series of corporate failures. Consequently, this has led to reform in the auditing regulatory framework. This study examines the impact of the auditing regulatory reforms, in particular, the impact of the independent audit inspection on the auditing profession. This is ascertained by analysing the views expressed in response to the discussion paper titled, ‘Promoting Audit Quality’ published by the Financial Reporting Council (FRC), and from interviews with selected audit partners in the United Kingdom. Using deprofessionalisation as a framework, the analysis highlights the conflict of jurisdiction over the work between the regulator and the audit practitioners, the challenge to the profession’s control over the professional knowledge base by the regulator, and the crisis of ideology of the members of the profession. The evidence suggests a trend towards deprofessionalisation of the auditing profession that may diminish auditors’ professional attributes and their social role to the public.